IL11 (Interleukin-11) Causes Emphysematous Lung Disease in a Mouse Model of Marfan Syndrome. Issue 5 (27th April 2023) - Ng, Benjamin; Xie, Chen; Su, Liping; Kuthubudeen, Fathima F.; Kwek, Xiu-Yi; Yeong, Daryl; Pua, Chee Jian; Cook, Stuart A.; Lim, Wei-Wen
Abstract : Background: Marfan Syndrome (MFS) is an inherited connective tissue disorder caused by mutations in the FBN1 (fibrillin-1) gene. Lung abnormalities are common in MFS, but their pathogenesis is poorly understood. IL11 (interleukin-11) causes aortic disease in a mouse model of MFS and was studied here in the lung. Methods: We examined histological and molecular phenotypes in the lungs of Fbn1 C1041G/+ mice (mouse model of Marfan Syndrome [mMFS]), an established mouse model of MFS. To identify IL11-expressing cells, we used immunohistochemistry on lungs of 4- and 16-week-old Fbn1 C1041G/+ : Il11 EGFP/+ reporter mice. We studied the effects of IL11 inhibition by RT-qPCR, immunoblots and histopathology in lungs from genetic or pharmacologic models: (1) 16-week-old IL11 receptor (IL11RA) knockout mMFS mice ( Fbn1 C1041G/+ : Il11ra1 −/− mice) and (2) in mMFS mice administered IgG control or interleukin-11 receptor antibodies twice weekly from 4 to 24 weeks of age. Results: mMFS lungs showed progressive loss and enlargement of distal airspaces associated with increased proinflammatory and profibrotic gene expression as well as matrix metalloproteinases 2, 9, and 12. IL11 was increased in mMFS lungs and localized to smooth muscle and endothelial cells in young mMFS mice in the Fbn1 C1041G/+ : Il11 EGFP/+ reporter strain and in fibroblasts, in older mice. In mMFS mice, genetic ( Fbn1 C1041G/+ : Il11ra1 −/− ) or pharmacologic (anti-interleukin-11 receptor) inhibition of IL11 signaling reduced lung emphysema, fibrosis, and inflammation. This protective effect was associated with reduced pathogenic ERK1/2 signaling and lower metalloproteinase 2, 9, and 12 expression. Conclusions: IL11 causes lung disease in mMFS. This reveals a shared IL11-driven disease mechanism in lung and aorta in MFS and suggests inhibition of IL11 signaling as a holistic approach for treating multiorgan morbidity in MFS.